1998
DOI: 10.1007/bf03173087
|View full text |Cite
|
Sign up to set email alerts
|

The development of first graders' reading skill as a function of pre-school motivational orientation and phonemic awareness

Abstract: This study examined the development of reading skill during the first school year. The predictors were pre-school motivational orientations, coping tendencies, knowledge of the alphabet and phonemic awareness. From 151 pre-school children (6 years of age) rated by pre-school teachers on motivational orientations, 32 non--readers were allocated according to their dominating motivational disposition to one of the following extreme groups: task orientation, social dependence, ego-defensive, and multiple non-task-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 36 publications
2
34
2
4
Order By: Relevance
“…Task orientation at the beginning of Grade 1 was a significant predictor of word recognition at the end of Grade 1. Furthermore, some studies have found that task-focused behaviour in kindergarten was a significant predictor of word-reading skill in Grade 1 (Dally, 2006;Salonen, Lepola, & Niemi, 1998), even after controlling for the effects of kindergarten phonological awareness.…”
Section: Task-focused Behaviour and Learning To Readmentioning
confidence: 96%
“…Task orientation at the beginning of Grade 1 was a significant predictor of word recognition at the end of Grade 1. Furthermore, some studies have found that task-focused behaviour in kindergarten was a significant predictor of word-reading skill in Grade 1 (Dally, 2006;Salonen, Lepola, & Niemi, 1998), even after controlling for the effects of kindergarten phonological awareness.…”
Section: Task-focused Behaviour and Learning To Readmentioning
confidence: 96%
“…Similarly, Salonen, Lepola and Niemi (1998) showed that, among the preschool motivational orientations, task orientation was the most important predictor of subsequent word reading skill. By following students with diverging reading careers from preschool to grade 2, Lepola, Salonen, and Vauras (2000) showed that progression in word reading was related to increased task orientation and decreased non-task orientation, whereas relative impairment was associated with decreased task orientation and increased social dependence.…”
Section: Motivation and Problems In The Acquisition Of Reading And Mamentioning
confidence: 96%
“…Previous research has shown that engagement in reading is related to reading achievement (Guthrie & Wigfield, 2000). Moreover, Salonen et al (1998) showed that children who displayed functional achievement beliefs at kindergarten progressed to a greater degree in their reading skill in 1st grade compared to those with more dysfunctional beliefs. Furthermore, Onatsu-Arvilommi and Nurmi (2000) showed that achievement beliefs and behaviours and reading performance, form cumulative developmental cycles.…”
Section: Achievement Beliefs and Behaviours In Reading Acquisitionmentioning
confidence: 97%